Islamic HRM, creativity and innovativeness: workplace happiness as a mediator - Wok, Saodah; Hashim, Junaidah (2016)
This study investigates the relationship between Islamic HRM, creativity and innovativeness with workplace happiness as its mediating effect. Seven hypotheses were formulated and investigated through triangulation method which involves document analysis, interview and survey. The population of this study are 509 Muslim employees and 172 Muslim HR managers in large and medium-sized organisations representing various sectors in Malaysia. There are three phases of data collections. Based on the data collected, it is proven that workplace happiness acts as a mediator between Islamic HRM and innovativeness and creativity. The implications of the study are discussed.